Faire hirak à Paris. Les mises en scène d’une révolution contre le « système algérien » - Didier Le Saout (L’Année du Maghreb)
The rallies organized every Sunday in Paris since February 2019 on the Place of République to demand the « departure of the system » in Algeria implement a public protest action that combines digital collective commitments in virtual communities, commitments in communities constituted by personal links in collectives, political associations or parties, as well as individual commitments that make the individual a protest subject. All these modalities of action express the reluctance of the protesters to connect to an ideology. They converge in the production of an « anti-system » identity on which protest initiatives are organized.